The impact of workplace partnership: Becton Dickinson. Issue 9 (5th August 2014) - Totterdill, Peter; Exton, Rosemary
Abstract : Purpose: – This case study aims to demonstrate how the fortunes of companies and plants can be turned around when management and unions work together to release the knowledge, experience and creativity of the workforce. Design/methodology/approach: – Becton Dickinson (BD) has produced medical devices in Drogheda, Ireland, for 50 years, but during the first decade of this century, the plant seemed to be falling off the parent company's radar. Substantial job losses and a lack of new investment left a space inside the factory "the size of a football field". Employment had fallen to less than a hundred and corporate interest was waning. Findings: – The problem was tackled by the 'IDEAS Institute' a trade union initiative developed "to identify ways in which new thinking and new services can be introduced into the workplace for the benefit of employees and the enterprise as a whole". Originality/value: – The IDEAS Institute held a series of meetings with BD employees, union representatives and management, leading to the creation of the Joint Union-Management Steering Team (JUMST) where both parties were equally represented. Drawing on inclusive dialogue with employees at every level, JUMST defined the future vision for Drogheda and identified the first cluster of improvement projects designed to show that the factory could again become a key performer within the BD group. The case study offers persuasive evidence that workplace partnership means more than good industrial relations. Unions can play a key role in engaging workers at all levels in innovation and improvement, creating win-win outcomes for employees and their employers.